2005
DOI: 10.1111/j.1475-2743.2005.tb00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of fallow, tillage and manure application on soil organic matter and nitrogen fractions and on sorghum yield under Sudano‐Sahelian conditions

Abstract: Abstract. Soil organic matter (SOM) controls the physical, chemical and biological properties of soil and is a key factor in soil productivity. Data on SOM quantity and quality are therefore important for agricultural sustainability. In 1990, an experiment was set up at Saria, Burkina Faso on a sandy loam Lixisol to evaluate long‐term effects of tillage (hand hoeing or oxen ploughing) with or without 10 t ha−1 yr−1 of manure and fallowing on SOM and N concentrations and their distribution in particle size fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…In Zimbabwe, NRE ranged between 0.15 and 0.29 kg kg -1 when manure was applied alone or in combination with N fertilizer (Nyamangara et al 2003), while on a degraded sandy soil application of 17 Mg ha -1 poor quality manure alone could not supply sufficient nutrients to a maize crop (Chikowo et al 2004). Mando et al (2005) reported the long-term effects of tillage and manure application on sorghum in the Sudano-Sahelian conditions. The increase in yields was associated with increased N availability due to manure and greater water availability that improved the efficiency of use of the applied fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…In Zimbabwe, NRE ranged between 0.15 and 0.29 kg kg -1 when manure was applied alone or in combination with N fertilizer (Nyamangara et al 2003), while on a degraded sandy soil application of 17 Mg ha -1 poor quality manure alone could not supply sufficient nutrients to a maize crop (Chikowo et al 2004). Mando et al (2005) reported the long-term effects of tillage and manure application on sorghum in the Sudano-Sahelian conditions. The increase in yields was associated with increased N availability due to manure and greater water availability that improved the efficiency of use of the applied fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…In the Sudano-Sahelian zone of Burkina Faso, Mando et al (2005, b) observed that application of manure enhanced SOM concentration and increased Figure 3. Relative effects of differences in soil organic matter concentration in the root zone on crop growth and yield.…”
Section: Soil Organic Matter and Crop Yieldmentioning
confidence: 99%
“…However, a growing body of research in SSA uses the same study design to examine land management practices that may improve soil conditions (aggrade soils) from a degraded baseline. Such practices include (but are not limited to) communal grazing [126,127], tree plantations [93,128], and fallowing [96,129].…”
Section: Positive Trajectories and Conclusionmentioning
confidence: 99%